Fluorescent Carbon Particles formed from Concentrated Glucose Solutions. (17th January 2019) - Obadiya, Tomilola; Uppala, Harsh; Sidebottom, David
Abstract: Simple glucose solutions were heat treated in an attempt to produce carbon nanodots (CNDTs) with a monodisperse size distribution using a bottom-up approach. Absorption and fluorescence properties of the heat-treated solutions display remarkable similarity to CNDTs reported in the literature. However, particle-sizing and AFM measurements indicate the increasing fluorescence is accompanied by the growth of particles that are larger than most CNDTs discussed in the literature (a concentrated population of monodisperse 30 nm particles and a low concentration of much larger, roughly 500 nm, particles). A dialysis study, shows these larger particles are not responsible for the bulk of the optical properties but, rather the optical properties likely stem from molecular by-products that accompany the heating and caramelization of the sugar.